Nasopharyngeal s. pneumoniae carriage and density in Belgian infants after 9 years of pneumococcal conjugate vaccine programme. Issue 1 (2nd January 2018) - Wouters, Ine; Van Heirstraeten, Liesbet; Desmet, Stefanie; Blaizot, Stéphanie; Verhaegen, Jan; Goossens, Herman; Van Damme, Pierre; Malhotra-Kumar, Surbhi; Theeten, Heidi; ,
Graphical abstract: Highlights: High (>80%) pneumococcal carriage in infants in day-care or with acute otitis media. Carriage density was associated with antibiotic use and signs of common cold. Low (<6%) PCV13 vaccine serotype frequency, with 19F and 14 most often identified. Extremely low (<1%) PCV13 non-PCV10 serotype (3, 6A, 19A) frequency. Low frequency of antibiotic-resistant S. pneumoniae, except co-trimoxazole. Abstract: Background: In Belgium, the infant pneumococcal conjugate vaccine (PCV) programme changed from PCV7 (2007–2011) to PCV13 (2011–2015) and to PCV10 (2015–2016). A 3-year nasopharyngeal carriage study was initiated during the programme switch in 2016. Main objective of the year 1 assessment was to obtain a baseline measurement of pneumococcal carriage prevalence, carriage density, serotype distribution and antibiotic resistance. Materials/methods: Two infant populations aged 6–30 months and without use of antibiotics in the seven days prior to sampling were approached: (1) attending one of 85 randomly selected day-care centres (DCC); (2) presenting with AOM at study-trained general practitioners and paediatricians. Demographic and clinical characteristics were documented and a single nasopharyngeal swab was taken. S. pneumoniae were cultured, screened for antibiotic resistance and serotyped, and quantitative Taqman real-time PCR (qRT-PCR) targeting LytA was performed. Results: Culture-based (DCC: 462/760; 60.8% – AOM: 27/39; 69.2%) and LytA- based (DCC: 603/753; 80.1% – AOM: 32/39; 82.1%) carriage prevalence was high. Average pneumococcal DNA load in LytA -positive day-care samples was 6.5 × 10 6 copies/µl (95%CI = 3.9–9.2 × 10 6, median = 3.5 × 10 5 ); DNA load was positively associated with signs of common cold and negatively with previous antibiotic use. Culture-based frequency of 13 pneumococcal vaccine (PCV) serotypes was 5.4% in DCC and 7.7% in AOM, with 19F and 14 being most frequent, and frequencies below 0.5% for serotypes 3, 6A, 19A in both populations. Predominant non-PCV serotypes were 23B and 23A in day-care and 11A in infants with AOM. In day-care, resistance to penicillin was rare (<0.5%) and absent against levofloxacin; 32.7% and 16.9% isolates were cotrimoxazole- and erythromycin-resistant respectively. Conclusion: Four years after PCV13 introduction in the vaccination programme, PCV13 serotype carriage was rare in infants throughout Belgium and penicillin resistance was rare. Continued surveillance in the context of a PCV programme switch is necessary.